2003
DOI: 10.1182/blood-2002-09-2683
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ribosomal and translation-associated genes is correlated with a favorable clinical course in chronic lymphocytic leukemia

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) is a heterogenous disease with a highly variable clinical course. Recent studies have shown that CD38 surface expression on the malignant cell clone may serve as a prognostic marker in that CD38 ؉ patients with B-CLL are characterized by advanced disease stage, lesser responsiveness to chemotherapy, and shorter survival than CD38 ؊ patients. To further investigate the molecular phenotype of these 2 clinical subgroups, we compared the gene expression profiles of CD38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 25 publications
4
52
2
1
Order By: Relevance
“…27,28 cDNA samples were purified by phenol/ chloroform/IAA/PLG extraction, precipitated and used to generate biotinylated cRNA by in vitro transcription for 16 hr at 37°C (Bioarray High Yield RNA Transcript Labeling Kit; Enzo Life Sciences, Farmingdale, NY). Purification of cRNA was done using RNeasy mini columns (Qiagen).…”
Section: Expression Analysismentioning
confidence: 99%
“…27,28 cDNA samples were purified by phenol/ chloroform/IAA/PLG extraction, precipitated and used to generate biotinylated cRNA by in vitro transcription for 16 hr at 37°C (Bioarray High Yield RNA Transcript Labeling Kit; Enzo Life Sciences, Farmingdale, NY). Purification of cRNA was done using RNeasy mini columns (Qiagen).…”
Section: Expression Analysismentioning
confidence: 99%
“…In the study of Welsh et al (2001), it was shown that those rapidly growing tumors cell lines and the most poorly differentiated ovarian tumors were grouped together by hierarchical clustering analysis, and exhibited a relative underexpression of ribosomal genes. Similarly, Du¨rig et al (2003) noticed that a large number of ribosomal and other translation-associated genes were coordinately overexpressed in CLL patients with more favorable clinical outcome. Several previous studies suggested that FTCs harboring a PAX8-PPARg are likely to be histologically more aggressive compared to those without the rearrangement (French et al, 2003;Nikiforova et al, 2003).…”
Section: Pax8-ppar (+) Ftcs Pax8-ppar (-) Ftcsmentioning
confidence: 99%
“…The synthesis of double-stranded cDNA and the generation of the biotinylated cRNA was done according to Durig et al 14 Fragmentation of cRNA, hybridization of samples to Rat Expression Set 230A Affymetrix GeneChip microarrays (Affymetrix, Santa Clara, CA), washing, staining and scanning of the arrays in a GeneArray scanner (Agilent, Palo Alto, CA) were performed as recommended in the Affymetrix Gene Expression Analysis Technical Manual, 2000 (http://www. affymetrix.com/support/index.affx).…”
Section: Preparation Of Glomerular Total Rna and Gene Expression Analmentioning
confidence: 99%